PraktikalCute Enterprise / Muhammad Qayyum Mohd Azman - Mohd Azman, Muhammad Qayyum (2021)
Business opportunities are about how we related the case study and business and apply it on our business plan to be a successful entrepreneur and how we identify any course of production of beginning until end. It also teaches us the strategic plan to recognize any problems with this business. . By the way, I would like to thanks my lecturer and my supportive friends because without their help, I can’t finish my business opportunity. At the end of the case study, I managed write a lot about PraktikalCute Enterprise. Based on the case study that I wrote, we managed to know that PraktikalCute Enterprise was make handmade craft business. Firstly, I sold a product from PraktikalCute Enterprise which is handmade keychain. Other than that, I also sold boxy pencil case. This product is a big pencil case which can put many things in it. Next, I also sold facemask strap. This item is for women that use facemask during this pandemic Covid-19. Otherwise, I also sold 3 Layer Facemask with Filter Slot. This is for someone that didn’t love to wear a basic facemask. This facemask also has a slot to put the filter so I can guarantee that this facemask can save our self from this covid-19. Last but not least, I also sold a sling beg for men. This bag is suitable for male student or some men that is work in office. When I started to sold that item, I figure out that my communication skills with someone I didn’t know was improved. Otherwise, I also learn how to handle many types of customer and I only can have that experience when I handle a business. In the same time, I also know how to promote my item in social media. Lastly, I will show you what I have sold within 1 month. I managed to get RM 260 total sales within 1 month.